Snowdrift and other stories - Heyer, Georgette (Naperville, IL Sourcebooks Casablanca, 2017)
Collects fourteen stories of romance, intrigue, and villainy, including "Pistols for two," "A husband for Fanny," and "Runaway match."
Snowdrift -- Full moon -- Pistols for two -- A clandestine affair -- Bath miss -- Pink domino -- A husband for Fanny -- To have the honour -- Night at the inn -- The duel -- Hazard -- Pursuit -- Runaway match -- Incident on the Bath Road.
105374
Keywords: Short stories, English; Man-woman relationships -- Fiction; Regency -- England -- Fiction; England; Short stories; Romance fiction; Historical fiction; Regency fiction; Fiction